Diário de um detento: nas fronteiras do gênero testemunho - Pereira, Luciara (2009)
The aim of this work was to investigate the genre testimonio, in its social, political and cultural Hispanic-American context from the 60 s; which has evidenced significant resonances in the Brazilian publishing market. However, the trajectory of this model of representation raises a series of discussions aiming to understand its anatomy , mainly because its fundamental peculiarity is giving way to voices which are aside the cultural and political process and take the written word to reveal a significant event in the constitutive process of their group. In addition, it s necessary to consider that, from its emergence to its institutionalization and migration to other cultural spaces, this genre acquires functions and distinct senses. It is the case of A Prisioner s Diary: the book, 2001, from Jocenir, used here to analyze a literary work which illustrates the testimonio in Brazil. This book presents some situations related to the prison s routine, which carry the intention to make public the marginal experience, represented by an individual who is not acquainted to the literate conventions. It is in this circumstance that lies most of the impasses to be established, as there is a constant process of negotiation between dissonant social-cultural contexts, necessary to guarantee the insertion of this narrative in the literate space.